Spacetime and the Dream of Consciousness : Relational Ontology and Quantum Theories of Mind - Jokela, Niko (My University, 2025)
This thesis addresses the mystery of consciousness and the perceived lack of meaning in science, exploring how these themes are intertwined. It investigates whether consciousness is best understood as a fundamental feature of reality rather than as a byproduct of the brain—an inquiry framed by the long-standing debate between idealism and materialism. Various anomalous and so-called paranormal phenomena are considered as indications that idealist interpretations may provide a stronger explanatory framework. Drawing on both scientific and philosophical theories, the thesis examines how quantum mechanics—particularly Carlo Rovelli’s relational interpretation—can be understood as reflecting attributes of consciousness itself. This relational perspective has already gained traction in contemporary science, and it resonates with historical and modern forms of idealism, which regard the universe and its laws as emerging from a fundamental substrate of consciousness. The thesis engages with recent proposals in idealist and quantum consciousness research, including the work of Donald Hoffman, Federico Faggin, Mauro D’Ariano, and Stuart Hameroff and Roger Penrose. Building on these insights, it develops a new synthesis that seeks to unify aspects of quantum mechanics, idealism, and materialism into a coherent theoretical framework. This synthesis portrays spacetime as akin to a dream, with living beings as the dreamers who both generate and inhabit it. From this perspective, the logic of the world resembles dream logic, where appearances are not what they seem but conceal deeper relations, and where meaning is grounded in how reality is felt rather than how it merely appears. The thesis concludes that such a view offers a paradigm capable of restoring meaning to scientific inquiry while deepening our understanding of consciousness and reality.
Keywords: Consciousness Studies, Idealism, Materialism, Relational Quantum Mechanics, Quantum Consciousness, Dreams